Early immune outcome of retroperitoneal laparoscopic radical nephrectomy for localized renal cell carcinoma: a prospective, randomized study - Lu, Yang; Tianyong, Fan; Qiang, Wei; Xiaobo, Cu; Siyuan, Bu; Ping, Han (Canadian Urological Association Journal, 2012)
Objectives: We evaluated differences in cytokine responses and T-lymphocyte subsets following retroperitoneal laparoscopic andconventional open radical nephrectomies for localized renal cellcarcinoma (RCC). Methods: A total of 62 patients with T1N0M0 staged RCC were randomized to either retro-laparoscopic (n = 31) or open (n = 31) radical nephrectomy. Plasma levels of interleukin-1β (IL-1β), IL-6, andtumour necrosis factor-alpha (TNF-α) were measured separately by enzyme linked immunosorbent assay (ELISA) preoperatively and on postoperative days 1 and 5. Levels of CD3+, CD4+ and CD8+ as well as the CD4+:CD8+ ratio were acquired by flow cytometry at the same time points. Results: Levels of IL-1β, IL-6 and TNF-α increased significantly compared to preoperative values in both groups (p < 0.05) on postoperative day 1, and all the parameters in the open group were significantly higher than those in the retro-laparoscopy group (p < 0.05). On postoperative day 1, the levels of CD3+ and CD4+ and the CD4+:CD8+ ratio decreased markedly compared to preoperative values for both groups (p < 0.05). Elevations of the CD4+:CD8+ ratio in the retro-laparoscopy group (p < 0.05) and the CD8+ level in the open group (p < 0.05) were observed when compared with the other group. On postoperative day 5, the levels of CD3+ and CD4+ and the CD4+:CD8+ ratio in the retro-laparoscopy group, as well as the level of CD8+ in the open group, returned to about preoperative levels (p < 0.05). Follow-up ranged from 4 to14 months postoperatively in all 62 patients with a 100% cancer specific survival rate in both groups. Conclusions: Retroperitoneal laparoscopic radical nephrectomy is associated with the milder cytokine responses caused by trauma and inflammation and the better preserved distribution ofT-lymphocytes.